Struktur Semantis Verba “melaksanakan” dalam Bahasa Jawa Kuno - Eka Sura; Ni Ketut Ratna Erawati (Program Magister Linguistik Universitas Udayana, 2020)
This research article focuses in analyzing the semantic structure of the verb